A Critical review of women’s consumption and empowerment in China - Wang, Simei; Kim Ling, Geraldine Chan; Azlina Abdullah, (Penerbit Universiti Kebangsaan Malaysia, 2024)
As Chinese women become more educated and participate in the labor force, they earn more money independently. At the same time, thanks to China's one-child policy, women have gained more intergenerational wealth. The economic foundation allowed Chinese women to play bigger power in the consumer market, and a phenomenon called "Her Economy" since 2007. The improvement of discourse power and economic empowerment of Chinese women in the consumer market rendered them better achieve self-empowerment. However, female behavior is also shaped by society, and female consumption is more likely to be influenced by consumer culture and become the background board of consumer society, and women find it difficult to achieve real empowerment through consumption. Although the existing literature has explored this issue, the research field has not been extended to Chinese female consumers, and the theoretical perspective of empowerment is lacking. Thus, this paper reviews women’s consumption and empowerment in China from a critical perspective.